2011
DOI: 10.5539/ijbm.v6n10p256
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions towards Distributed Leadership in School Improvement

Abstract: In spite of the sizable growth in the number of empirical studies tackledthe distributed form of leadership over the past decade, the bulk of this research isa case study. Relatively few published studies have investigated the impact of distributed leadership on school improvement; therefore, the current paper attempts to investigate TESOL teachers'perceptions towards distributed leadership and school improvement. The theoretical framework for this study is grounded on the multifactor transformational/transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(27 reference statements)
0
6
0
3
Order By: Relevance
“…I pushed them to move forward and aspire for excellence. (Interview: Jiyun-jiyun 02)Jiyun-jiyun was regarded as a “charismatic” leader (Shakir et al., 2011), who energized followers with a clear sense of purpose and articulated vision. Ling-ling displayed more “individualized considerations” (Shakir et al., 2011), and she focused on caring for the needs of each individual teacher and faculty member and worked continuously to coach and guide them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…I pushed them to move forward and aspire for excellence. (Interview: Jiyun-jiyun 02)Jiyun-jiyun was regarded as a “charismatic” leader (Shakir et al., 2011), who energized followers with a clear sense of purpose and articulated vision. Ling-ling displayed more “individualized considerations” (Shakir et al., 2011), and she focused on caring for the needs of each individual teacher and faculty member and worked continuously to coach and guide them.…”
Section: Resultsmentioning
confidence: 99%
“…The researcher designed and developed the interview protocol from the empirical studies on teacher leaders and leadership (e.g. Bailey et al., 2008; McGee et al., 2014; Shakir et al., 2011). The interview protocol included two parts.…”
Section: Methodology and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu, ia merupakan cara yang lebih lestari untuk membina iklim yang berfokus pada pembelajaran (Leithwood et al, 2004;Spillane, 2006) dan membina kapasiti untuk pergerakan organisasi (Ancona et al, 2009;Hallinger & Heck, 2010). Pendapat ini turut disokong oleh Menurut Shakir et al, (2011). Mereka mendapati, terdapat dua kelebihan kepimpinan distributif kepada sekolah.…”
Section: Kepimpinan Distributifunclassified
“…In the earlier years of studying distributed leadership in an educational setting, it was difficult to determine the impact of this approach on school improvement efforts (Bolden, 2011); however, studies are finding that distributed leadership is a key factor in school improvement efforts (Heck & Hallinger, 2010;Shakir, Issa, & Mustafa, 2011). Research has also shown that distributed leadership is a shared characteristic in successful action research programs in schools (Glanz, 2005;Price & Valli, 2005).…”
Section: Collaborative Action Researchmentioning
confidence: 99%